SEGMENTATION OF SOCIETY AS AN OBJECT OF PROSELYTIZING ACCORDING TO THE QURAN - Moh. Lukman Hakim; Nur Syam (Jurnal Al-Bayan: Media Kajian dan Pengembangan Ilmu Dakwah, 2022)
Da'wah is an invitation or call to the truth of Islam in a wise way. From several aspects in the element of da'wah, one of the important elements that must be considered in this activity is the object of the da'wah itself. Differences in the background and environment of the society as the object of da'wah require the da'i to really understand the segmentation of the society itself in an effort to be able to formulate the da'wah methods and materials that are most suitable for the mad'u Using a library research approach, this research was conducted to describe the segmentation of society as an object of da'wah according to the Qur’an. From the results of this study, it was found that in general it was explained that the segmentation of society as the object of da'wah was divided into two namely Muslims and non-Muslims, Muslims were divided into two groups, enlightened and misguided then strong and weak in their faith, while non-Muslims were divided into four groups, atheists, disbelievers/polytheists, Jewish/Christian and hypocrites. Besides that, in the Qur'an, it is also explained that there is a special group that must be prioritized, namely family and close relatives. So overall there are three segmentation of objects of da'wah. Keywords: Society, Da’wah, Qur’an